Analisis SWOT Pentingnya Fasilitas Dan Layanan Lembaga Keuangan Bank Konvensional Di Kecamatan Singojuruh - Prasetyo, Nur; Hidayati, Nuri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2024)
One sector that can realize regional economic development includes the presence of financial institutions which are often considered the heart and driving force of a country's economy. This can be seen in the lack of banking financial institutions in the Singojuruh District area until now, so that it has an impact on regional income such as handling tax payments, salaries, pensions or other financial transactions related to bank financial institutions carried out in other areas close to Singojuruh District, Banyuwangi Regency. This type of research is descriptive qualitative. The type of method used in this research is field methods (field research). In this study, the data that has been collected is analyzed using the Internal Factor Evaluation (IFE) and (EFE) Matrix. For identification in this research, the SWOT matrix is ​​used internally and externally. The conclusion is to expand a representative banking network, take advantage of regional, land and educational advantages with the availability of mobile banking services, optimize the performance of human resources to speed up the process of banking product services and information and expand the reach of banking services or units.